Early human impact on soils and hydro-sedimentary systems: Multi-proxy geoarchaeological analyses from La Narse de la Sauvetat (France). (December 2020) - Mayoral, Alfredo; Granai, Salomé; Develle, Anne-Lise; Peiry, Jean-Luc; Miras, Yannick; Couderc, Florian; Vernet, Gérard; Berger, Jean-François
We analysed the late-Holocene pedo-sedimentary archives of La Narse de la Sauvetat, a hydromorphic depression in the southern Limagne plain (central France), where chronologically accurate studies are scarce. The multi-proxy geoarchaeological and palaeoenvironmental analysis of two cores from different areas of the basin was carried out through sedimentological, geochemical, micromorphological and malacological investigations. Integration of these datasets supported by a robust radiocarbon-based chronology allowed discussion of socio-environmental interactions and anthropogenic impacts from Late Neolithic to Early Middle Ages. Until the Middle Bronze Age, there was no clear evidence of anthropogenic impact on soils and hydro-sedimentary dynamics of the catchment, but two peaks of high alluvial activity probably related to the 4.2 and 3.5 kyr. BP climate events were first recorded in Limagne. Significant anthropogenic impacts started in the Late Bronze Age with increased erosion of the surrounding volcanic slopes. However, a major threshold was reached c. 2600 cal BP with a sharp increase in the catchment erosion interpreted as resulting from strong anthropogenic environmental changes related to agricultural activities and drainage. This implies an anthropogenic forcing on soils and hydro-sedimentary systems much earlier than was usually considered in Limagne. These impacts then gradually increased during Late Iron Age and Roman periods, but environmental effects were certainly contained by progress in agricultural management. Late Antiquity environmental changes are consistent with regional trend to drainage deterioration in lowlands, but marked asynchrony in this landscape change suggests that societal factors implying differential land management were certainly predominant here.